The Impact of Counseling Based On the PLISSIT Model on Sexual Function of Infertile Women: A Clinical Randomized Controlled Trial - Sara Daeichin; Mozhgan Khalili; Marzieh Bagherinia; Mansour Rezaei; Ali Akbar Parvizifard (Journal of Midwifery & Reproductive Health, 2022)
Background & aim: Infertility has negative effects including sexual dysfunction in infertile women. This study investigated the effect of counseling based on the PLISSIT model on sexual function of infertile women.Methods: This study was performed on 60 infertile women, who were randomly assigned to two intervention (direct and indirect counseling) and control groups (20 in each group). In the direct counseling group, the intervention included four face to face sexual counseling sessions, once a week, based on the PLISSIT model. In the indirect counseling group, the similar content of counselling was given through booklet and the participants received telephone counseling. Sexual function was measured using female sexual function index (FSFI) pre and four weeks after intervention. One-way ANOVA was used to compare the groups before the intervention and ANCOVA with control of the baseline score after the intervention.Results: There was no significant difference between the sexual function of three groups at baseline. After the intervention, by controlling the baseline score, a significant difference was observed in the overall score of sexual function in the direct counseling group (mean difference: 5.1, 95% CI: 26.3 to 29.7, P=0.001). In the indirect counseling group, after the intervention, only a significant differences was observed in the pain dimension (mean difference: 0.9, 95% CI: 2.5 to 3.9, P=0.044).Conclusion: It seems that PLISSIT based direct counseling improves more the sexual function of women with infertility. So, it is recommended that such counseling program be integrated into the health care program of infertile women.